Treatment of Chronic Hepatitis C Infection among Current And Former Injection Drug Users within a Multidisciplinary Treatment Model at a Community Health Centre - Adam I Newman; Shelley Beckstead; David Beking; Susan Finch; Tina Knorr; Carol Lynch; Meredith MacKenzie; Daphne Mayer; Brenda Melles; Ron Shore (Canadian Journal of Gastroenterology)
The aim of the present prospective observational study was to assess uptake and success of hepatitis C virus (HCV) treatment among a group of former and current injection drug users with chronic HCV infection at the Street Health Centre in Kingston, Ontario. The Street Health Centre offers hepatitis C education, assessment and treatment within a multidisciplinary, integrated and collaborative treatment model of care delivered by primary care professionals. The study enrolled a convenience sample of 34 patients. Seventy per cent of study patients had no postsecondary education, 85% were unemployed and one-third were unstably housed. A majority of study patients self-reported mental health problems. Of the 14 patients who initiated antiviral treatment in the study period, eight (57%) achieved sustained virological response. Regardless of virological outcome, patients who initiated treatment showed positive trends toward increased social and psychiatric stability, and decreases in high-risk behaviours. These results suggest that not only is successful treatment of chronic HCV infection in current and former injection drug users with concurrent psychiatric disorders possible, but the benefits of such treatment delivered in a community-based, multidisciplinary, primary care model may extend beyond narrowly defined virological outcomes.